Beneficial effects of Gynostemma pentaphyllum honey paste on obesity via counteracting oxidative stress and inflammation: An exploration of functional food developed from two independent foods rich in saponins and phenolics. (July 2022) - Chen, Sinan; Liu, Xinyan; Zhao, Haoan; Cheng, Ni; Sun, Jing; Cao, Wei
Graphical abstract: Gynostemma pentaphyllum honey paste (GH) enhanced the palatability of G. pentaphyllum with the application of honey, and affected oxidative stress, inflammation and gut microbiota via possible synergistic effects of saponins and phenolics to alleviate high-fat diet (HFD)-induced obesity in mice. Highlights: GH enhanced the palatability of G. pentaphyllum with the application of honey. The saponins of G. pentaphyllum and the phenolics of honey may act synergistically to attenuate obesity. GH alleviated oxidative stress by regulating the expression of inflammatory cytokines and NF-κB, thereby reducing inflammation and ameliorating obesity. GH modified the gut microbial structure of obese mice. Abstract: The development of functional foods that possess a combination of biological functions and good sensory properties is an emerging topic in the field of food and function. Gynostemma pentaphyllum ( G. pentaphyllum ) is widely considered to exert anti-obesity effect owing to its abundant saponins and other bioactive components, but bitter and unacceptable taste limit its utilization. While honey, a natural sweetener, not only has the pleasure sense but is also usually used as the carrier of functional food due to its phenolic oligosaccharide, etc. In the present study, we proposed the preparation method of a G. pentaphyllum honey paste (GH) and its beneficial effects on obese mice. The results showed that GH contented 0.055 mg/g Gypenoside XLIX, 0.01 mg/g Gypenoside A, and 11 kinds of phenolics. It could down-regulate 23.3% of liver TC level, increase serum ALT activity, improve liver tissue damage and epididymal adipocyte hypertrophy than obese mice. Besides, GH regulated enzyme activities such as SOD and GSH to enhance oxidative stress defense and exerted anti-inflammatory activity via IL-6 (52.4%), TNF-α (38.7%), IFN-γ (32%) and NF-κB (28%) genes down-regulation, which also reshaped the gut microbiota structure, exerting anti-obesity effects. More importantly, GH promoted obese mice appetite with orexin-A compared to G. pentaphyllum alone. This study provided a new perspective on the development of G. pentaphyllum functional foods with both good organoleptic performance and obesity therapy.